The Influence of Perceived Convenience and Perceived Benefits on Loyalty Through SIM Card User Satisfaction by.U - Hikmah Ramadhani; Eka Bertuah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the relationship between the influence of Perceived Convenience and Benefits on Loyalty Through Sim Card User Satisfaction By.U. Path analysis is an analytical approach applied in this study and the sample method used is purposive sampling of 150 respondents who are Sim Card By.U users. The results of this study indicate that perceived convenience and perceived benefits have a direct influence on user satisfaction. And perceived convenience, perceived benefits, and user satisfaction have a direct influence on loyalty. There is an indirect effect of perceived convenience, perceived benefits on user loyalty through user satisfaction. However, perceived user satisfaction cannot be an intervening variable between perceived convenience and user loyalty